Initial assessment of mortality rates of burn patients in a tertiary care hospital by total body surface area, depth and facial burns, and its correlation with serial total leucocyte count - Balachandran, Kavitha Jayanthi; Nirmalanandan, Manoj Kumar (International Surgery Journal, 2020)
Background: The pattern of burns in victims varies with the manner of infliction of burns. Age plays an important role in deciding the mortality and morbidity of burn victims. Other factors that decide the prognosis of burn victims are the total body surface area (TBSA), Depth of burns, and inhalational injury as evidenced by facial burns. Assessment of these epidemiological factors and inhalational injury can be done as a part of the initial evaluation. Such an assessment aid in resuscitation including emergent airway and decision making regarding the need for skin grafts or escharotomy. Serial measurement of total leucocyte count also helps in identifying the onset of infection and progress to septicaemia and increased mortality rates. Methods: As a part of the initial evaluation, we attempt to study the relation between TBSA, Depth of burns, facial burns, and total WBC count with mortality. A background of septicaemia was also noticed in the majority of patients. Results: For analysis, patients were divided into two groups- Survivors and Non-survivors. A fall in total WBC count coincided with the onset of sepsis and mortality. The other three factors also had a direct correlation with mortality rates. Conclusions: A scoring system constituting all the factors is essential as an initial diagnostic step and it will help in deciding early intubation, escharotomy, and aggressive fluid resuscitation.